The Economic Gap of Muslims: The Challenges of Globalization and Sharia Solutions - Arini Alfa Hidayah; Muallif Masyhuri (Journal of Global Islamic Economic Studies, 2024)
The economic disparity of Muslims is a crucial issue that is increasingly emerging in the era of globalization. Globalization on the one hand opens up opportunities for market access, investment, and technology for Muslim countries, but on the other hand deepens social inequality and dependence on the capitalistic economic system that is contrary to Islamic values. This research aims to analyze the challenges of globalization on the economy of Muslims and explore solutions based on sharia economics that can be implemented in an applicative and sustainable manner. Using a descriptive qualitative approach with literature study techniques, this study examines various relevant scientific sources to identify the root of the problem and formulate a solution strategy that is in accordance with sharia principles. The results of the study show that the economic inequality of the people is influenced by the weak Islamic financial literacy, the lack of optimal management of zakat and waqf, and the lack of regulatory support and technological innovation in the Islamic economic ecosystem. Instruments such as zakat, infaq, alms, and waqf have great potential as a mechanism for wealth redistribution, while digitalization and integration of sharia technology play a role in expanding financial inclusion. This study recommends the need for synergy between government stakeholders, Islamic financial institutions, educational institutions, and the community as well as strengthening affirmative policies and Islamic economic education to address systemic disparities. This research makes an academic and practical contribution in strengthening the sharia economy as a just, inclusive, and sustainable alternative solution in the midst of globalization challenges.